Using economic selection index for trait prioritization in sweetpotato target product profiles in Eastern Africa - Okello, Julius J.; Mwanga, Robert O.M; Yada, Benard; Ssali, Reuben; Hareau, Guy; Campos, Hugo (CGIAR, 2024)
This brief reports an approach that relies on market intelligence gathered from a broad spectrum of breeding program customers, taking market forces into account when computing trait economic selection indexes (ESI). The ESIs generated are then used to prioritize the traits pursued in the breeding program. The pilot study targeted the white-, orange-, and purple-fleshed market segments in the Lake Victoria crescent in Eastern Africa—a region that faces high virus pressure. Along with virus protection, target product profiles (TPPs) designed for these segments emphasize agronomic traits and nutritional enhancement (with vitamin A and anthocyanins). The ESI findings stress the heterogeneity of actors with divergent needs, underscoring the importance of trait prioritization in TPPs based on market forces and employing systematic market intelligence to understand trait preferences of market segment actors/participants.